Incredible Kerala? A Political Ecological Analysis of Organic Agriculture in the "Model for Development" - Sapna Elizabeth Thottathil (University of California, Berkele, 2012)
In 2010, the South Indian state of Kerala’s Communist-led coalition government, the Left Democratic Front (LDF), unveiled a policy to convert the entirety of the state to organic farming within ten years; some estimates claim that approximately 9,000 farmers were already participating in certified organic agriculture for export at the time of the announcement. Kerala is oftentimes hailed as a “model for development” by development practitioners and environmentalists because of such progressive environmental politics (e.g., McKibben 1998). Recent scholarship from Political Ecology, however, has christened organic farming as a neoliberal project, and much like globalized, conventional agriculture (e.g., Guthman 2007 and Raynolds 2004). Drawing from fourteen months of fieldwork in Kerala between 2009-2011, I explore this tension between Kerala as a progressive, political “model,” and globalized, corporatized organic agriculture. I utilize Kerala’s experiences with organic farming to present another story about North-South relations in globalized organic farming. In contrast to recent Political Ecological work surrounding alternative food systems, I contend that organic agriculture can actually offer meaningful possibilities for transforming the global agricultural system in local places. Using Polanyian (1944) and Gramscian (1971) understandings of civil society and social change, I argue that Kerala’s agrarian crisis of the 1990s, stemming from the commodification of Kerala’s agrarian environment and the intensification of chemical-based, cash crop agriculture, stimulated an ecological countermovement in the late twentieth century. This crisis included several farmer suicides and pesticide-poisoning from Endosulfan. Kerala’s civil society and political institutions actively developed this countermovement by relying on an existing institutional structure that supports redistributive reforms, and a history of political organizing by Kerala’s Left. This ecological countermovement is now comprised of organic farming institutions (e.g., vanguard certification-centered bodies such as the Indian Organic Farmers Producer Company Limited (IOFPCL)) and policies (e.g., Kerala’s 2010 Organic Farming Policy), that are re-embedding market-driven agriculture ecologically and socially. To augment my Polanyian analysis, I also utilize analytics from Global Commodity Chain and Global Value Chain scholarship, and rely on Cultural Political literature and the work of several Kerala scholars (e.g., Heller 1999 and Herring 1983), to argue that Kerala’s organic farming movement is promoting the civic engagement of organic farmers in agricultural governance. Kerala’s Organic Farming Policy, for example, represents an alternative form of state-led development that prioritizes local-level decision making. Finally, I explore the bifurcation of Kerala organic farming countermovement between proponents of Kerala’s Organic Farming Policy and certified organic farming for export; each defines organic farming differently. I contend that this divide is not “natural,” but the result of a conjuncture of agrarian cultural politics, an “imaginary” of Kerala as a biodiverse “hotspot,” existing political priorities, 1and political economic and geographic changes in places like Wayanad District. This evidence illustrates that countermovements occur on and are shaped by terrains with history, and are far from monolithic. These findings also trouble the idealization of Kerala as a “model,” and demonstrate that organic farming politics can take on different forms throughout the world, contingent on local and global factors and dynamics. I conclude, however, that Kerala’s organic movement does not have a predetermined future: it is neither destined to be a “model” nor homogenized and conventionalized by the forces of globalization. Evidence from Kerala instead elucidates that organic agriculture can offer a valid critique of chemical-dependent capitalist agriculture, but not necessarily in the way that current Political Ecological thought would prescribe.